Wybrane problemy implementacji nowych systemów rachunku kosztów w przedsiębiorstwach - Wroński, Paweł (Selected Problems in Implementing New Cost Accounting Methods in Enterprises, 2005)
Changes occurring in enterprises, in conditions of integrated European markets require from managers to make decisions based on substantial costs information on the business activity. This article presents summary results of questionnaire research on using and implementing cost accounting methods in managing companies. Research was carried out in 31 enterprises which have ISO 9000:2000 in the Lublin Region, in the years: 2002 and 2004. The conclusions concern problems of implementation of cost accounting and management accounting methods, factors restrictive in using cost accounting in management and the main direction of improvement in management cost accounting methods in those enterprises.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 382-390